The effect of filler content on properties of clamshell filled polyester composites / Mohd Zul Hanif Zamri - Hanif Zamri, Mohd Zul (2020)
The development of natural filler reinforced composite-based products to replace the engineering material is a trend in engineering application. The benefit of using clamshell natural filler in composites is give high performance in term of mechanical properties. The objectives of this study to study on the production of polyester mix composites with various clam shell loadings such as 0, 10, 20, 30,40 and 50 phr respectively. It also to characterize clam shell – unsaturated polyester composite by FTIR spectrometer shows peak at 1082.77 cm-1 for untreated and 1082.74 cm-1 for treated is characterized as the C-O stretching bond structure from the functional group of alcohol to analyse the effect of various clamshell on properties of clamshell – unsaturated polyester composite. The composites were prepared using hand lay-up method. This clamshell filler composites were evaluated for mechanical properties by tensile, impact and density testing and the properties are compared with control sample and different loading filler. In this research 10 phr is a higher tensile strength and impact strength at 39.55 MPa and 55.21 J/m than the other amount of clamshell loading used in the unsaturated polyester resin as well as controlled sample. Besides, the density of composite with 10 phr is lower compared to the other filler loading which is 0.48 g/cm3 .